AN EMPIRICAL STUDY ON AWARENESS AND CONSUMPTION PATTERN OF ORGANIC FOOD IN BENGALURU CITY, THE IT CAPITAL OF INDIA: AN ANALYSIS WITH RESPECT TO DIFFERENT DEMOGRAPHIC FACTORS AND AVAILABILITY OF ORGANIC FOOD PRODUCTS IN BENGALURU - Chattopadhyay, Anwesha; Khanzode, Priyanka (International Journal of Research -GRANTHAALAYAH, 2019)
Last 5 years have seen lots of changes in the consumption pattern of individuals with concerns rising constantly on the quality of climate conditions, individuals have become aware about change in climate, increasing pollution, deteriorating air quality, excessive use of chemicals in the farms, increase of carbon particles in environment and impact on population. Consumers now-a-days are very particular about the products they are consuming, Thus the concept of organic food product come into picture. This concept is gaining impetus in society especially after increase in health problems in individuals. It refers to using such food product which are eco-friendly and safe. The paper is a humble attempt to understand the level of awareness about organic food products in Bengaluru. This paper also aims at understanding the consumption pattern of individuals in Bengaluru. Statistical tools like ANOVA, Regression analysis, Chi-square tests and different charts are used to analyse the data obtained from a primary survey conducted in Bengaluru. On the basis of analysis done in the paper, it is concluded that the consumption has increased lately although more awareness should be created to make the consumption more popular among consumers.